Effect of Digital Payments on Consumer Behavior Mediated by Trust among Jombang High School Students - Chalimatus Sa’Diah; Shanti Nugroho Sulistyowati (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The increasing use of digital payment systems among senior high school and vocational school students has raised concerns about their potential influence on consumptive behaviour through convenience, accessibility, and transaction efficiency. This study aims to analyze the effect of digital payment usage on consumptive behaviour among students in Jombang and examine the mediating role of trust in usage. A quantitative explanatory approach was employed, involving 362 respondents selected through purposive sampling. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that digital payment usage significantly affects trust in usage but does not directly influence consumptive behaviour. Meanwhile, trust in usage significantly influences consumptive behaviour and mediates the relationship between digital payment usage and consumptive behaviour. These findings indicate that digital payment usage shapes students’ consumptive behaviour indirectly through the formation of trust in digital payment systems. The study contributes to digital financial behaviour literature by demonstrating the mediating role of trust in explaining how digital payment adoption may influence adolescent spending tendencies. The practical implications emphasize the importance of strengthening digital financial literacy, responsible spending awareness, and critical understanding of digital transaction risks among students to promote healthier financial behaviour in the digital economy.